Diagnosing respiratory syncytial virus using immunofluorescence and immunohistochemistry methods in caprine lungs with bronchopneumonia - Ceribasi, S.; Ozkaraca, M.; Ozer, H.; Ceribasi, A. O. (Ecole Nationale Veterinaire Toulouse, 2013)
The aim of this study was to evaluate the diagnostic interest of direct immunofluorescence and immunohistochemistry for RSV infection in goats with bronchopneumonia from the Elazig region. For this purpose, lungs of 889 slaughtered male hair goats were macroscopically analysed in order to looking for chronic bronchopneumonia lesions. Among the 146 cases of bronchopneumonia found in which mild lesions (according to the extent of consolidation) were prominent (65.8%), there were 105 interstitial bronchopneumonia, 41 catarrrhal-purulent bronchopneumonia and 2 verminous bronchopneumonia according to histological criteria. The RSV antigens were detected in 7 cases with interstitial chronic bronchopneumonia using direct immunofluorescence on frozen secions whereas direct immunohistochemistry on paraffine sections failed to detect the viral particles. These results show that immunofluorescence on frozen section was undoubitously more adequat than immunohistochemistry for RSV detection in situ and they suggest a possible role of RSV in the induction of interstitial bronchopneumonia in goats.
Keywords: Respiratory syncytial virus; goat; lung; chronic bronchopneumonia; pathology; diagnosis; immunofluorescence; immunohistochemistry